(untitled) (CIPEEX, 2025)
Objective: to analyze the relationship between body profile and the development of geriatric syndromes in the elderly population. Method: This is an integrative review. The search for articles was conducted in the National Library of Medicine and National Institutes of Health (PubMed) database. Results: The body profile of elderly people, assessed using BMI, whether related to malnutrition or overweight/obesity, is intrinsically related to the occurrence of geriatric syndromes, creating a state of vulnerability and, sometimes, poly-morbidities and polypharmacy that facilitate the development, above all, of cognitive impairment, sphincter incontinence, and postural instability. Conclusion: although there is a possible incidental relationship between body profile and geriatric syndromes, further studies on this topic and greater vigilance regarding the nutrition of the elderly population are still needed in order to better control BMI and the risk of developing syndromes.